A. \(S = \frac{{{2^{100}} - 1}}{{{2^{99}}{a^2}}}\)
B. \(S = \frac{{a\left( {{2^{100}} - 1} \right)}}{{{2^{99}}}}\)
C. \(S = \frac{{{a^2}\left( {{2^{100}} - 1} \right)}}{{{2^{99}}}}\)
D. \(S = \frac{{{a^2}\left( {{2^{99}} - 1} \right)}}{{{2^{99}}}}\)
C
Dễ thấy \({S_1} = {a^2};\,\,{S_2} = \frac{{{a^2}}}{2};\,\,{S_3} = \frac{{{a^2}}}{4};...;{S_{100}} = \frac{{{a^2}}}{{{2^{99}}}}\)
Như vậy \({S_1},\,{S_2},{S_3},...,\,{S_{100}}\) là cấp số nhân với công bội \(q = \frac{1}{2}\)
\(S = {S_1} + {S_2} + ... + {S_{100}} = {a^2}\left( {1 + \frac{1}{2} + \frac{1}{{{2^2}}} + ... + \frac{1}{{{2^{99}}}}} \right) = \frac{{{a^2}\left( {{2^{100}} - 1} \right)}}{{{2^{99}}}}\)
Câu hỏi trên thuộc đề trắc nghiệm dưới đây !
Copyright © 2021 HOCTAP247